Development of Android-Based E-Modules in Basic Computer and Networking Subjects for Class 10 Vocational High School Students: Pengembangan E-Modul Berbasis Android Pada Mata Pelajaran Komputer dan Jaringan Dasar Untuk Siswa SMK Kelas 10 - Izzathy Aisyah Efendi; Rahmania Sri Untari (Universitas Muhammadiyah Sidoarjo, 2022)
The use of android-based learning facilities as teaching materials for students is a solution to facilitate understanding of practicum material in online learning. This study aims to determine the development and feasibility of an Android-based E-module in computer and basic network subjects at SMK 1 Antarctica, Sidoarjo. This type of research is Research and Development (R&D) using the Analysis, Design, Development, Implementation, Evaluation (ADDIE) development model. The feasibility test was carried out by media experts and material experts as well as the results of student responses, the results of the validity of this study obtained a percentage of 94% in the